Extramedullary paraspinal hematopoiesis in hereditary spherocytosis - Gogia P; Goel R; Nayar S (Annals of Thoracic Medicine, 2008)
Hereditary spherocytosis (HS) is a common inherited hemolytic anemia due to red cell membrane defects. Extramedullary hematopoiesis is a compensatory response to insufficient bone marrow blood cell production. The preferred sites of extramedullary hematopoietic involvement are the spleen, liver and lymph nodes; but in HS, the posterior paravertebral mediastinum is also commonly involved. We report a case of a 50-year-old male who presented to us in respiratory distress and with bilateral paravertebral posterior mediastinal masses, which on trucut biopsy were found to be extra-hematopoietic masses; and the patient was found to have hereditary spherocytosis.